Avoiding damage caused by soil-structure interaction lessons learnt from case histories - Kastner, Richard; Standing, Jamie; Kjekstad, Oddvar (Thomas Telford, 2003)
Increasing development in the urban environment and supporting infrastructure systems has necessitated a greater use of underground space and sites that were hitherto judges to be not economically viable (e.g. because of difficult ground conditions). This presents many challenges in terms of planning, design and construction as well as the protection of existing buildings.